Carley UNHCR 1999.
Is an educational tool designed to tackle things such as Cultural differences and exile of children aged 5-8. -- Carley flees from ____home. All alone she sets Out to find help - other lands. She encounters the stone eaters, smokey crows and silk tall. But non of the end help her because she is stranger and different from the seven min. animated film narrated of action. Mike Ferriols.